(untitled) (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
Trust is often regarded as the cornerstone of influencer marketing success. When consumers perceive influencers as credible, honest, and relatable, they are more likely to consider their recommendations trustworthy. Trust in an influencer stems from multiple dimensions, such as expertise, authenticity, attractiveness, and similarity to the audience. This study employs a systematic literature review (SLR) methodology to investigate the effectiveness of influencer marketing by examining the relationship between consumer trust and purchase intentions on social media. This study explored the effectiveness of influencer marketing by analyzing the relationship between consumer trust and purchase intentions on social media platforms. The findings from the literature review demonstrate that trust is a critical mediator in determining the success of influencer marketing strategies. Influencers who exhibit authenticity, credibility, and expertise are more likely to foster trust among followers, which in turn significantly enhances consumers’ willingness to engage with and purchase the promoted products or services.